FILOSOFI PENDIDIKAN PANCASILA DALAM MERDEKA BELAJAR DAN IMPLEMENTASINYA PADA PEMBELAJARAN BAHASA INDONESIA - Ahmad Saiqu Dikri; Aldila Rahmita Putri; Dewi Maf’ula; Dewinda Citra Kesuma; Fani’Matur Rohmah; Selviana Dinda Widia Rizqi; Didin Widyartono; Ahmad Saiqu Dikri; Aldila Rahmita Putri; Dewi Maf’ula; Dewinda Citra Kesuma; Fani’Matur Rohmah; Selviana Dinda Widia Rizqi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
This research aims to understand the philosophy of Pancasila education in the context of independent learning and its implementation in Indonesian language teaching. The objectives are (1) to analyze the philosophy of Pancasila education in independent learning according to Indonesian educational philosophers, and (2) to determine the implementation of the philosophy of Pancasila education in independent learning in Indonesian language teaching. This research is a literature review conducted by exploring the thoughts of philosophers regarding Pancasila education in independent learning. Data collection techniques involve reading literature that contains relevant information on the research topic, such as journals, research reports, newspapers, books, and others. The references are then processed using Content Analysis method, focusing on the objective, systematic, and generalizable construction of content or messages. Based on the research findings, it can be concluded that: (1) the educational concepts advocated by figures such as KH Hasyim Asy'ari, KH Ahmad Dahlan, and Paulo Freire share similarities in emphasizing the importance of education that emancipates humans, and (2) the implementation of the Independent Learning concept in Indonesia, such as independent curriculum, student-centered learning, holistic assessment, inclusive schools, and the use of technology in teaching, aligns with the ideas of these educational figures.